Income taxation and job creation - Johanna Röhrs (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)
In this paper, I argue that there is an inefficiently high number of job creators in a model with labour market imperfections and an endogenous decision to become a job creator. I therefore augment the standard labour matching model developed by Mortensen and Pissarides by an endogenous job decision that is based on heterogeneous job creation abilities. In the decentralised market, job creators can appropriate large parts of the surplus from matches therefore making job creation too attractive relative to the firstbest. It can hence be welfare enhancing to tax the profits from job creation. The introduction of a tax on the profits of job creators restores the firstbest allocation by affecting the job decision. It drives rather unproductive job creators out of the market since the marginal job creator is affected and not the average one. Thus, the negative effects to job creation are small. Moreover, the tax does not distort vacancy posting and hiring choice of firms.
Keywords: H21; J21; J64; L26; 330; optimal taxation; imperfect labour markets; job creation; entrepreneurship